Keterkaitan While Collar Crime dengan Coorporate Crime - Deamonika Deamonika; Nur Annisa (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
White collar crime is a crime committed by respected people, while corporate crime is a crime related to corporations. White collar crime and crinre corporations have also always been linked to the crime economy. White collar crime can be controlled by corporations, therefore a type of crime arises, namely corporate services. The research method is literature study, the aim is to find out what forms of crime are categorized as "white collar crime", the result is that the application of the law given to perpetrators of "white collar crime" crimes has provided justice and legal certainty to the community.